Semi Prime hesitant fuzzy submodule - A. Fadhil . J; Walaa Hassan . A (Genius Journals, 2022)
In this paper, we study the definition of hesitant fuzzy set, with some of its properties and introduce the definition of semi prime hesitant fuzzy submodule with the result equivalent of definition . We proved the image and the inverse image of the concept above with respect to the homomorphism between modules , finally we proved all the relationships between these concepts.
Keywords: hesitant fuzzy set; hesitant fuzzy module; Prime hesitant fuzzy; Semi